Children’s Rights in the Council of Europe – Framework - Vlašković, Veljko (Children’s Rights in Regional Human Rights Systems, 2024)
The Council of Europe aims to connect the countries of the European continent to promote the idea of human rights and liberties to achieve common social development and progress in the rule of law for all countries and their citizens. In this context, the Council of Europe provides a comprehensive normative framework for the implementation and protection of child rights as a distinct category of human rights. Under the auspices of the Council of Europe, a significant number of international treaties and soft law instruments have been created that are of direct or indirect importance to child rights. The rights of the child have been recognised, applied, and protected first in treaties on human rights in general, and then in family related conventions, and particularly within child oriented treaties. In terms of child rights, the activities of various judicial or non-judicial bodies that monitor or supervise the implementation of these treaties or act separately within the Council of Europe’s framework should be considered. The real engine of the Council of Europe is the European Court of Human Rights, which has been continuously developing case law for human rights. Such an approach by the Court influences the harmonisation of the substantive family law of member States, including the exercise of the rights of the child. Over the last few decades, other international and supranational organisations have increasingly suppressed the Council of Europe. However, the significance of its work in the fields of human and child rights cannot be easily diminished.Keywords:  child rights, human rights, Council of Europe, treaties, child rights-oriented approach, soft law